Effects of Paving Technology, Pavement Materials, and Structures on the Fatigue Property of Double-Layer Pavements - Changqing Deng; Yingjun Jiang; Zhanchuang Han; Hongwei Lin; Jiangtao Fan (Advances in Materials Science and Engineering)
Double-layer paving technology, which is a new technology for construction asphalt pavements, has received increasing research attention for several years. However, few studies have focused on the effect of asphalt pavement layer thickness and mixture-type combinations on the fatigue properties of a double-layer pavement. Therefore, the fatigue properties of the double-layer and traditionally paved asphalt pavements were studied in this work. The effects of two paving technologies, three mixture combinations, and two asphalt layer thickness combinations on the fatigue properties of asphalt pavements were studied through bending beam tests, and a fatigue equation of different asphalt pavements was established using the two-parameter Weibull distribution. Subsequently, the fatigue lives of different pavements were compared and analyzed under the same cyclic load. Results indicate that the flexural strength and fatigue life of the double-layer pavement increased by at least 10% and 54%, respectively, compared with those of a traditionally paved pavement structure. The goodness of fit of the equation established using the Weibull distribution exceeded 0.90. For the traditional paving technology, compared with the pavement structure combination of 4-cm AC-13 surface layer/6-cm AC-20 bottom layer, the fatigue life of a 3-cm AC-13 surface layer/7-cm AC-20 bottom layer can be increased by at least 8%, while the fatigue lives of other pavement structures are reduced significantly. The results also indicate that the fatigue life of the double-layer pavement structure with the 3-cm AC-13 surface layer/7-cm AC-20 bottom layer can be increased by at least 114% compared with that of the traditionally paved pavement structure (4-cm AC-13 surface layer/6-cm AC-20 bottom layer). Additionally, the fatigue lives of other pavement structures can be improved. To effectively improve the fatigue life of an asphalt pavement, a double-layer pavement structure with the 3-cm AC-13 surface layer/7-cm AC-20 bottom layer combination is recommended.